Frailty as a Predictor of Cognitive Disorders: A Systematic Review and Meta-Analysis - Borges, Marcus Kiiti; Canevelli, Marco; Cesari, Matteo; Aprahamian, Ivan (Frontiers in Medicine, 2019)
Background/Aim: Current evidence in the literature supports associations between frailty, cognitive impairment and dementia. The study aim was to describe the risk of cognitive disorders associated with physical frailty in older adults from community-based studies. Methods: We performed a systematic review and meta-analysis, using MEDLINE, PsycINFO, Scopus and Web of Science as databases for the search. Cohort and longitudinal studies were included in qualitative analysis and quantitative synthesis. For inclusion, studies had to assess dementia and cognitive impairment as a primary or secondary outcome, and describe the prevalence of frailty among participants at baseline and follow-up. Results: Of the 2,210 studies retrieved by the systematic review, 6 relevant studies were included in a meta-analysis. Baseline frailty was significantly associated with an increased risk of geriatric cognitive disorders (pooled OR = 1.80, 95% CI = 1.11-2.92; p = 0.02). Heterogeneity across the studies was significant (I2 = 79%). Conclusions: The analyses confirmed that frail older adults were at higher risk of incident cognitive disorders than non-frail elders. Frailty status seems to be most associated with the risk of incident dementia. Frailty may represent a risk factor for dementia and could constitute a novel modifiable target in early cognitive impairment.